Kebijakan Belajar Mengajar Hybrid Muhammadiyah 10 di Masa Pemberlakuan PPKM di Surabaya - Indira Devi Anggraeni; Agus Machfud Fauzi (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2021)
The COVID-19 pandemic has hit all corners of the world, Indonesia is one of the Asian countries affected by the COVID-19 pandemic in various fields, one of which is the world of education. The education policy set by the government does not only have an impact on students but also has an impact on educators. During the Enforcement of Restrictions on Community Activities, the Minister of Education allows face-to-face teaching and learning activities for areas where PPKM level 1 – 3. See and describe the effectiveness and risks in changing mixed learning patterns carried out by educators and students. This study uses a qualitative method using literature study, interviews and observations as data collection techniques, the informants in this study were students and teachers of SMA Muhammadiyah 10 Surabaya. Action Rationality Theory which was initiated by Max Weber as a reference for analysis in this study. The assumption in the study refers to the policy of SMA Muhammadiyah 10 Surabaya in making decisions. Teaching and learning activities are carried out in a hybrid (mixed) manner, so offline and online learning are solutions and adaptations of new policies.